A 5 Year Study of Deaths Following Administration of Medically Prescribed Drugs: Diagnostic Dilemma and Challenges at Autopsy (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
A significant number of deaths occur worldwide due to medical error which is claimed to be the third leading cause of death after heart disease and cancer. Adverse drug reaction or events (ADR/ADE) which consists of drug toxicity, drug side effects and anaphylactic reactions to drugs are included in such deaths.[1] Concluding that death actually resulted from medical error or adverse drug reaction requires a thorough and detailed autopsy with supportive investigations for delivering justice to the bereaved parties. Deaths due to ADR’s is associated with diagnostic difficulties as there are only minimal and subtle morphological changes at autopsy which fade away with passage of time. The analysis of specific biochemical markers are not always possible due to lack of facilities. In such cases, the forensic pathologists rely on the autopsy findings and method of exclusion is used to arrive at a correct conclusion. This study is a retrospective analysis of 16 cases of deaths due to alleged medical negligence following medical administration of prescribed drugs, autopsied during a 5-year period from 2011 to 2015. The cases represented approximately 0.1% of all autopsy cases during that period. Data were analysed with regard to age, sex, alleged exposures, clinical symptoms, survival time, autopsy findings, cause of death and time since death.
Keywords: Autopsy; Adverse drug reaction; Anaphylaxis; Death investigation; Mortality; Medical negligence